Fairness, Incentives and Contractual Incompleteness - Ernst Fehr; Alexander Klein; Klaus M. Schmidt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2001)
We show that concerns for fairness may have dramatic consequences for the optimal provision of incentives in a moral hazard context. Incentive contracts that are optimal when there are only selfish actors become inferior when some agents are concerned about fairness. Conversely, contracts that are doomed to fail when there are only selfish actors provide powerful incentives and become superior when there are also fair-minded players. These predictions are strongly supported by the results of a series of experiments. Furthermore, our results suggest that the existence of fair actors may be an important reason why many contracts are left deliberately incomplete.
urn:nbn:de:bvb:19-epub-18-6
Keywords: C7; C9; J3; 330; Incentive Contracts; Moral Hazard; Fairness; Reciprocity; Incomplete Contracts